Shoulder and thorax kinematics contribute to increased power output of competitive handcyclists - Stone, B.; Mason, B. S.; Warner, M. B.; Goosey-Tolfrey, V. L. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Current knowledge on recumbent handbike configuration and handcycling technique is limited. The purpose of this study was to evaluate and compare the upper limb kinematics and handbike configurations of recreational and competitive recumbent handcyclists, during sport specific intensities.